Biomarker discovery of thalassemia and sickle-cell disease from blood peptidome - Dong, Xueming (2016)
This study aims to discover inherited blood disease biomarkers through peptidomic approaches, in order to develop faster and more economical diagnostic method suitable for population screening. 3 types of inherited blood diseases, thalassemia Hb CS, Hb E and sickle cell disease Hb S were included in this study. Hb CS markers were successfully identified through both MALDI-MS and LC-MS. 2 of the candidate markers were further analyzed by pseudo-MRM. Pseudo-MRM analysis demonstrated competitive sensitivity while further reduced total sample analysis time by approximately 25%. Hb E and Hb S markers were identified through LC-MS but not MALDI using same approaches. This study successfully identified several promising biomarkers for 3 different inherited blood diseases, thus provided support for biomarker discovery through peptidomic/degradomic approaches. Methods developed in this study could be readily expanded to biomarker discovery of other inherited blood diseases. Furthermore, as methods are compatible with MRM that is common in clinical laboratories, this study is readily converted to clinical applications.